Domestic workers across the world : global and regional statistics and the extent of legal protection. (ILO Publications, 2013)
The adoption of new international labour standards on domestic work (Convention No. 189 and its accompanying Recommendation No. 201) by the ILO at its 100th International Labour Conference in June 2011 represents a key milestone on the domestic workers. This publication sheds light on the magnitude of domestic work, a sector often "invisible" behind the doors of private households and unprotected by national legislation.